HISTORICAL INTERPRETATION OF SOCIETAL COHESION IN TAMIL TEMPLES - V. Biresan; V. Thirumurugan (RADJA PUBLIKA, 2025)
This article examines the historical role of Tamil temples in shaping the social cohesion of Tamil society from the Sangam era to the Chola and Vijayanagara periods. These temples were not only spiritual centers, but also institutions that played a role in economics, politics, and culture. This research examines how Tamil temples become symbols of cultural and social identity, integrating various levels of society through religious rituals, festivals, and Bhakti practices that emphasize spiritual equality. Additionally, these temples played an important role in the economy by managing land and resources, as well as contributing to the social structure by accommodating various caste groups. This study also explores the religious pluralism that occurs in Tamil Nadu, where Hindus, Jains and Buddhists interact with each other in a tolerant environment. By examining inscriptions and archaeological evidence, this article shows how Tamil temples have been centers of social cohesion, maintained cultural identity, and been a force in the socio-political dynamics of Tamil Nadu throughout history.